Evaluation of the new generation herbicide penoxsulam in transplanted rice(Oryza sativa L.) - Sasna S (Department of Agronomy, College of Agriculture, 2014)
The study entitled “Evaluation of the new generation herbicide penoxsulam in transplanted rice (Oryza sativa L.)” was conducted during the period, December 2012 to April 2013 at farmer’s field in Nemom block, Thiruvananthapuram district. The objective of the study was to assess the bio-efficacy of the post emergence micro herbicide penoxsulam in transplanted rice and to work out the economics. The experiment was laid out in randomised block design with eight treatments and three replications. Four doses of penoxsulam i.e. 17.5, 20.0, 22.5 and 25.0 g a.i ha-1 (T1 - T4 ), bispyribac sodium @ 30.0 g a.i ha-1 (T5 ), 2, 4 –D sodium salt @ 1 kg a.i ha-1 (T6), hand weeding twice (T7) and weedy check (T8) constituted the treatments. Study of the weed flora dynamics of experimental field indicated the dominance of broad leaved weeds (7 sp.), followed by sedges (3 sp.) and grasses (2 sp.) All the herbicide treatments reduced the population and biomass of weeds substantially over weedy check. The lowest density and dry weight of weeds and highest weed control efficiency was recorded with penoxsulam @ 25.0 g a.i ha-1 (T4) at all the stages of observation, viz., 20 DAT, 40 DAT and 60 DAT. With respect to density of weeds, T4 was found to be on par with T3 at 20, 40 and 60 DAT. Regarding dry weight of weeds, at 20 DAT, T4 was on par with T3 ; however, at 40 DAT, all other herbicide treatments were on par with T4. None of the herbicides produced any phytotoxic symptom on rice plant. Critical analysis of the growth factors indicated the favourable effect of weed control treatments especially penoxsulam @ 25.0 and 22.5 g a.i ha-1 on plant height at harvest, number of tillers at 40 and 60 DAT and dry matter production at harvest. All the weed control treatments significantly improved the yield attributes viz., number of productive tillers m-2, grain weight panicle-1 and significantly lowered the sterility percentage as compared to weedy check. Penoxsulam @ 22.5 g a.i ha-1(T3) registered highest grain yield (5404 kg ha-1), net income (Rs 49065 /- ha-1) and B:C ratio (1.67) which was on par with other doses of penoxsulam(T4 , T2 and T1) as well as bispyribac sodium @ 30.0 g a.i ha-1 (T5) and 2,4 - D sodium salt (T6). Even though hand weeding twice registered grain yield comparable to herbicide treatments, due to very high labour cost involved, net income and B:C ratio were significantly low for this treatment. The weedy check recorded significantly lower values for grain yield, net income and B:C ratio compared to herbicide treatments and the yield loss due to weeds in this treatment was 22.13 per cent. Enumeration of soil microbial population 6 days after herbicide spraying revealed that the herbicides caused an initial reduction in the population of bacteria; but, there was no significant variation in the population of fungi and actinomycets , compared to weedy check where the rhizosphere was undisturbed. Considering weed control efficiency, grain yield, net income and B:C ratio, the new generation herbicide penoxsulam @ 22.5 g a.i ha-1 at 10 DAT can be adjudged as the best treatment for weed management in transplanted rice.